Does China improve social welfare after implementing the national volume-based procurement? - Wang, Huan; Huo, Ya-Tong; Zhuang, Qian (Frontiers in Pharmacology, 2023)
Objective: To explore the changes in social welfare before and after the implementation of the national volume-based procurement (NVBP). Explore whether the NVBP promotes the healthy development of manufacturers under the premise of benefiting patients. Then put forward relevant suggestions on how to effectively intervene the government in the pharmaceutical market. Methods:Starting with consumer surplus and producer surplus, social welfare was studied from three perspectives of price, supply and demand. Results: Consumer surplus was significantly increased, and the drug welfare of patients was significantly improved. The profits of the whole pharmaceutical industry have decreased but will increase in the future. The welfare of individual pharmaceutical enterprises varies. Overall social welfare has been significantly improved. Conclusion: The core purpose of the NVBP is to improve the medication welfare of patients, and through the increase of consumer surplus, it can affect the increase of producer surplus. Under such a linkage mechanism, the diversified linkage system of "price, demand, and supply" will achieve the effect of "1+1+1>3".